Who is Ili-Rapiḫ: Brother or Son of Rib-Adda? - Abo-Eleaz, Mohy-Eldin E. (Antiguo Oriente, 2023)
The fate of Byblos during the Amarna Period in the last days of the reign of Rib-Adda was characterized by uncertainty and a significant series of events. Several questions regarding the personality of the leader of the rebellion against Rib-Adda and the nature of the family ties between the two can be raised. This study addresses the personality of Ili-Rapiḫ, who sent the letters EA 139-140 to Akhenaten and another to an official named Paḫura. It also discusses this important period in the history of Byblos and its relationships with Egypt through a re-sequencing of the dates of the letters. By following the proposed chronology, Ili-Rapiḫ can be identified as the son of Rib-Adda, not as a rebel against him.